SynCAM 1 improves survival of adult‐born neurons by accelerating synapse maturation. Issue 3 (1st October 2015) - Doengi, Michael; Krupp, Alexander J.; Körber, Nils; Stein, Valentin
ABSTRACT: The survival of adult‐born dentate gyrus granule cells critically depends on their synaptic integration into the existing neuronal network. Excitatory inputs are thought to increase the survival rate of adult born neurons. Therefore, whether enhancing the stability of newly formed excitatory synapses by overexpressing the synaptic cell adhesion molecule SynCAM 1 improves the survival of adult‐born neurons was tested. Here it is shown that overexpression of SynCAM 1 improves survival of adult‐born neurons, but has no effect on the proliferation rate of precursor cells. As expected, overexpression of SynCAM 1 increased the synapse density in adult‐born granule neurons. While adult‐born granule neurons have very few functional synapses 15 days after birth, it was found that at this age adult‐born neurons in SynCAM 1 overexpressing mice exhibited around three times more excitatory synapses, which were stronger than synapses of adult‐born neurons of control littermates. In summary, the data indicated that additional SynCAM 1 accelerated synapse maturation, which improved the stability of newly formed synapses and in turn increased the likelihood of survival of adult‐born neurons. © 2015 Wiley Periodicals, Inc.